Yahuarsónicos, visualización de su influencia en la escena musical urbana de Loja. Periodo 2008-2021 - Guiñaguazo León, Luis Ángel (2024)
Yahuarsónicos is one of the most relevant urban music groups of the city of Loja in the XXI century. In its more than fifteen years of trajectory they have become a reference for the conformation of a local scene, characterized by the composition of unpublished pieces framed by the fusion of diverse styles and genres with lyrics of social, humanitarian and sentimental character. Based on the above, the purpose of this work is to visualize and disseminate the influence of the group in question, through the study of its trajectory and discographic production. As a result of the field work, it was possible to elaborate information cards that compile data about the artistic characteristics present in the discography of Yahuarsónicos and that of other urban bands, with which we proceeded to make a comparative table between each one in order to find points in common, later we carried out the production of a video-documentary that contains historical material of photographic, audiovisual and sonorous nature of the group object of this study. After having completed the whole process described above, we obtained as a result the video-documentary "Yahuarsónicos en escena" that allows us to know the history, trajectory, discography, and legacy of this group in the XXI century Lojano fusion scene. Key words: Yahuarsónicos, music scene, music fusion, video-documentary.